Question

Solve the Differential Equation:

(2y^4 + xy)dx - (6x^2) dy= 0

Answer #1

solve the differential equation
(2y^2+2y+4x^2)dx+(2xy+x)dy=0

solve the differential equation...
(x2-1)(dy/dx)+xy=0

solve the bernqoulli equation dy/dx+xy+xy^2=0

Solve: (x^4 – xy^3)dy + (2y^4 – x^3y)dx = 0

solve differential equation ((x)2 - xy +(y)2)dx - xydy
= 0
solve differential equation (x^2-xy+y^2)dx - xydy =
0

solve (x^2+2y^2)dx/dy = xy

Solve the Homogeneous differential equation
(7 y^2 + 1 xy)dx - 1 x^2 dy = 0
(a) A one-parameter family of solution of the equation is y(x)
=
(b) The particular solution of the equation subject to the
initial condition y(1) =1/7.

1) Solve the given differential equation by separation of
variables.
exy
dy/dx = e−y +
e−6x −
y
2) Solve the given differential
equation by separation of variables.
y ln(x) dx/dy = (y+1/x)^2
3) Find an explicit solution of the given initial-value
problem.
dx/dt = 7(x2 + 1), x( π/4)= 1

differential equations solve
(2xy+6x)dx+(x^2+4y^3)dy, y(0)=1

Solve the differential equation write the answer without
fractions and negative exponents :
(6y+x^2y^11) dx - (x^3y^10-6x) dy = 0

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 3 minutes ago

asked 40 minutes ago

asked 40 minutes ago

asked 59 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago

asked 3 hours ago

asked 3 hours ago

asked 3 hours ago

asked 4 hours ago